The Arctic Sea Ice - Melting During Summer or not Freezing in Winter? - Skaret, Henriette Bærheim (The University of Bergen, 2016)
The Arctic sea ice cover has retreated rapidly during the last three decades, concurrent with recent global temperature increase both in the atmosphere and in the ocean. The sea ice cover has experienced a retreat in extent and a reduction in thickness, hence the sea ice volume is declining. As a consequence, the multi-year sea ice is decreasing, and first-year ice is now the dominating ice type in the Arctic Ocean. This study uses the Norwegian Earth System Model (NorESM), forced at the surface with atmospheric reanalysis data from the Coordinated Ocean-ice Reference Experiments phase II (CORE-II), during the period from 1948 to 2007. The model simulation is compared to available observations, both from satellites and in-situ observations, for model evaluation. Since there are large regional and seasonal differences of the sea ice cover in the Arctic, this study provides an evaluation of the regional and seasonal variations in 12 different Arctic regions, where March represents the winter (maximum sea ice cover in the Northern Hemisphere) and September represents the summer season (minimum sea ice cover in the Northern Hemisphere). There are particularly two 20-year periods in the model simulation with noticeable trends in sea ice extent, Period I (1948-1967) and Period III (1988- 2007), which are analyzed in more detail. The Barents Sea is in particular focus in this study, and the decreasing sea ice in this region is found to be associated with observed changes in temperature during these periods, both in the atmosphere and the ocean. The model simulation shows significant negative trends over the last 20 years, and there has been a loss of sea ice in all Arctic regions in the winter season as well as the summer season. However, the sea ice declines regionally and seasonally at different rates. Seven of 12 regions in the interior Arctic Ocean have more or less a full sea ice cover in all winters, and these regions are thus only contributing to the summer sea ice extent trends in the Northern Hemisphere. It is ...